Hubungan kebiasaan konsumsi dan status gizi dengan kejadian GERD pada mahasiswa saat puasa - Dwi Novri Supriatiningrum; Amalia Rahma; Eka Srirahayu Ariestining; Endah Mulyani; Sutrisno Adi Prayitno (Poltekkes Kemenkes Aceh, 2025)
Background: GERD is a pathological condition caused by the reflux of stomach contents into the esophagus. Diet is a factor in the occurrence of GERD in adults, including students and workers. Factors that cause GERD recurrence include stress and diet.Objectives: To determine the intake of micronutrients, fiber, frequency of tea consumption, and nutritional status during the fasting month on the occurrence of GERD in students.Methods: Observational quantitative research method with a cross-sectional research design, purposive sampling data collection. Respondents numbers were 81 people fasting and students at the Faculty of Health, Universitas Muhammadiyah Gresik. This Research in Health Faculty, Universitas Muhammadiyah Gresik. Data collection through interviews with 2x24 hour food recall questionnaires, Food Frequency Questionnaire (FFQ), calculation of Body Mass Index (BMI) and Gastroesophageal Reflux Disease Questionnaire (GERD-Q). Data analysis used the Shapiro-Wilk test and Spearman test.Results: Respondents were aged between 18 years and 24 years. The statistic test with spearman test showed a relationship between tea-drinking habits (p=0,010) and noodle consumption habits (p=0,001) with GERD. Analysis of the relationship between intake of fiber (p=0,472), micronutrient intake of vitamin A (p=0,228), vitamin C (p=0,964), calcium (p=0,471), iron (p=0,647), zinc (p=0,757), and nutritional status (p=0,594) with GERD.Conclusion: There is a relationship between tea-drinking habits and the habit of consuming noodles and GERD. There was no relationship between intake of fiber, vitamin A, vitamin C, calcium, iron, zinc, and nutritional status with GERD.